Robotic assisted VATS lobectomy for loco-regionally advanced non-small cell lung cancer - Turner, Simon R.; Latif, M. Jawad; Park, Bernard J. (Video-Assisted Thoracic Surgery, 2017)
Despite lung cancer screening programs and efforts at early detection, patients with non-small cell lung cancer continue to present with loco-regionally advanced disease. In particular, patients with positive mediastinal lymph nodes (N1/2, stage II/IIIA) present a challenge to the thoracic surgeon. The thorough lymphadenectomy required by these patients can be difficult to perform with standard VATS approaches. In addition, hilar fibrosis may result from the neoadjuvant therapy these patients generally receive, which complicates dissection of the vascular and bronchial structures. The robotic approach offers benefits that can help to address these challenges. While not ideal for the surgeon just learning robotic surgery, in experienced hands this is an effective tool to deal with loco-regionally advanced lung cancer safely and with optimal oncologic efficacy.